Cardiac manifestations in myotonic dystrophy type 1 - A. G. Klementieva; E. K. Erokhina; K. V. Shamtieva; E. A. Melnik; A. N. Khrobostova; M. B. Filipenko; A. A. Arakelyants; T. V. Peters; E. P. Pavlikova (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To characterize cardiac damage in myotonic dystrophy type 1 (MD1), which is the most common form of hereditary primary muscular pathology in adults.Material and methods. Forty-eight patients with MD1 (31 men, 17 women, mean age 39,2±9,3 years) underwent clinical examination, neuropsychological examination, lipid profile assessment, electrocardiography (ECG), Holter ECG monitoring, and echocar-diography. Four clinical cases are presented that demonstrate clear cardiac manifestations of MD1.Results. The patients did not complain of arrhythmias or chest pain, while 7 (14,6%) had complaints of exercise shortness of breath. Cardiac conduction disorders occurred in 18 (37,5%) patients, which were represented by firstand second-degree atrioventricular (AV) block, his bundle and intraventricular conduction disturbances. According to Holter monitoring, heart rate <60 bpm was recorded in 46 (95,8%) patients, of which 2 (4,2%) were <30 bpm. One (2.1%) patient had atrial fibrillation. According to echocardiography, ventricular enlargement was detected in 3 (6,3%) patients, and atrial enlargement — in 8 (16,7%). None of the patients had an ejection fraction <50%.Conclusion. Cardiac involvement is a common manifestation of MD1. Full cardiac examination can help not only improve the quality of life of patients, but also avoid possible side effects of the prescribed treatment.